A novel nanosilica/graphene oxide hybrid and its flame retarding epoxy resin with simultaneously improved mechanical, thermal conductivity, and dielectric properties1. Issue 18 (14th May 2015) - Wang, Rui; Zhuo, Dongxian; Weng, Zixiang; Wu, Lixin; Cheng, Xiuyan; Zhou, Yu; Wang, Jianlei; Xuan, Bowen
<x xml:space="preserve">Abstract</x> A novel nanosilica/graphene oxide hybrid was prepared, which can simultaneously improve the typical properties (dielectric, thermal conductivity, thermal stability, and mechanical properties) and flame retardancy of epoxy resin.